Pengaruh Pendapatan Asli Daerah, Dana Alokasi Umum Dan Dana Alokasi Khusus Terhadap Indeks Pembangunan Manusia Dengan Belanja Modal Sebagai Variabel Intervening - Adel Riviando; Henri Agustin; Halmawati Halmawati (Jurnal Eksplorasi Akuntansi, 2019)
This research aims to prove empirically the influence of PAD, DAU and DAK on the HDI with Capital Expenditure as an Intervening variable. This is quantitative descriptive research. The population in this research were 19 districts and cities in the Province of West Sumatra in 2015-2017. The PAD variable is measured by the PAD formula =% allocation forming the HDI × total PAD, the DAU variable measured by the DAU formula =% allocation forming the HDI × the total DAU, the DAK variable measured DAK formula =% allocation of HDI maker × total DAK, variable Capital Expenditures measured by Capital Expenditure =% allocation of HDI formers × total Capital Expenditures and HDI measured through the average of 3 components forming the HDI. Samples in this study were determined by the total sampling method. The type of data used is secondary data obtained from www.bps.go.id and www.djpk.depkeu.go.id. The analytical method used is Partial Least Square. The results of this study shows that PAD, DAU and DAK have a significant positive effect on the HDI, Capital Expenditures are not able to mediate the influence of PAD, DAU and DAK on the HDI